2020
DOI: 10.2478/raon-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative radiotherapy versus surgery alone for retroperitoneal sarcomas: a systematic review and meta-analysis

Abstract: BackgroundThere is no clear evidence on whether radiotherapy (RT) improves treatment result in patients with retroperitoneal sarcomas (RPS).MethodsA systematic literature search was performed using PubMed, Scopus and CENTRAL databases. Data were retrieved from published comparatives studies in patients with RPS undergoing surgery alone or RT plus surgery. The primary endpoints were the 5-year OS and the median OS. The secondary endpoints were the recurrence-free survival (RFS) and the R0-resection rate. Contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…In extremity STS, pre- and post-operative RT have equivalent local control and overall survival outcomes [ 2 , 3 , 4 ]. Thus, pre-operative RT is often preferred as patients developed fewer long-term irreversible RT complications than those who received post-operative radiotherapy [ 5 , 6 , 7 ]. Nonetheless, pre-operative RT in STS management seldom results in tumour shrinkage, except for certain subtypes such as myxoid liposarcomas [ 8 , 9 , 10 , 11 ], and serves mainly to decontaminate the microscopic diseases surrounding the visible tumour.…”
Section: Introductionmentioning
confidence: 99%
“…In extremity STS, pre- and post-operative RT have equivalent local control and overall survival outcomes [ 2 , 3 , 4 ]. Thus, pre-operative RT is often preferred as patients developed fewer long-term irreversible RT complications than those who received post-operative radiotherapy [ 5 , 6 , 7 ]. Nonetheless, pre-operative RT in STS management seldom results in tumour shrinkage, except for certain subtypes such as myxoid liposarcomas [ 8 , 9 , 10 , 11 ], and serves mainly to decontaminate the microscopic diseases surrounding the visible tumour.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that NeoRT and AdjRT improved OS and 5-year OS compared to surgery alone [weighted mean difference (WMD): −22.93; 95% CI: −27.91, −17.96; P<0.0001] and (WMD: −18.93; 95% CI: −19.13, −18.74; P<0.0001), comparatively. Median RFS was also significantly increased in patients treated with either surgical resection and NeoRT or surgical resection (WMD: 0.19; 95% CI: 0.11, 0.33; P<0.0001) and AdjRT (WMD: 0.49; 95% CI: 0.32, 0.75; P=0.001) compared to surgery alone (45).…”
Section: Radiotherapy Schedulesmentioning
confidence: 94%
“…6 Due to the rarity and heterogeneity of RPS, there is a paucity of prospective data to inform the role of RT in a multimodality treatment approach. 73 The recently published preoperative radiotherapy plus surgery versus surgery alone for patients with primary retroperitoneal sarcoma (EORTC 62092: STRASS) trial did not show a statistically significant abdominal recurrence-free survival benefit for the addition of RT to surgical resection. 56 Post hoc exploratory analyses were conducted to evaluate whether specific histopathologic subtypes of RPS were more or less likely to benefit from preoperative RT.…”
Section: What Is the Role For Rt In The Treatment Of Rps And What Are The Preferred Dose Regimens And Treatment Planning Considerations Imentioning
confidence: 97%